Implementation of the Itsbat of Marriage in Terms of Law Number 1/1974 and Compilation of Islamic Law - Maskawati Maskawati; Sitti Harlina Hamid; Burhanudin Burhanudin (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study evaluates the implementation of marriage rituals at the Watansoppeng Religious Court following Law Number 1/1974 and the Compilation of Islamic Law. It evaluates the basis for judges' considerations in deciding marriage cases at the Watansoppeng Religious Court. This research is qualitative research with purposive sampling, and data collection techniques used are field research and library research. The data analysis technique was analyzed qualitatively, then described descriptively by explaining, describing, and describing the problems closely related to this research—the need to provide information and counseling to the community on an incentive basis. Counseling regarding the contents of Law Number 1/1974 concerning marriage, counseling on the importance of marriage registration for life to come, especially for their children and the assets they gain in marriage. This counseling is given to all levels of society, especially rural communities, both married and unmarried. The purpose of marriage to form an eternal family based on the Almighty God is achieved.